2019
DOI: 10.21067/mpej.v3i2.3761
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Assessment for Learning Integration in Scientific Approach Towards Students’ Conceptual Understanding on Work and Energy

Abstract: This study aims to determine the effect of the integrated assessment for Learning (AfL) which is assisted by the Tryout application in scientific approach on students' conceptual understanding. This study used a quasi-experimental method with a pretest-posttest control group design. This research was conducted at a high school in Malang with a sample of two classes by a random cluster sampling technique. There were two classes involved, namely one as an experimental class (using an integrated AfL assisted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…These results strengthen previous research, the concept of work and energy that is the most difficult for students is the mechanical energy of the system. This opinion is also supported by research results Elisa et al, (2019) who also stated that conservation of mechanical energy was the most difficult concept for students.…”
Section: Discussionsupporting
confidence: 54%
“…These results strengthen previous research, the concept of work and energy that is the most difficult for students is the mechanical energy of the system. This opinion is also supported by research results Elisa et al, (2019) who also stated that conservation of mechanical energy was the most difficult concept for students.…”
Section: Discussionsupporting
confidence: 54%
“…Although many students find physics challenging, its principles must be applied daily [42]. Students with a robust conceptual understanding can more effectively comprehend physics theories, principles, and laws [49].…”
Section: Conceptual Understandingmentioning
confidence: 99%
“…Further supporting the findings of this study, earlier research suggests that AFL through FLM can improve students' conceptual understanding of physics. Research by Elisa et al [49] team identified a significant difference in students' understanding of physics concepts between pretest and post-test scores. This study supports the idea that learning connected to AFL can enhance students' understanding of essential physics concepts, particularly those related to work and energy.…”
Section: Conceptual Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this will help in creating a more effective learning strategy so that students will not find it difficult (Thompson et al, 2011), One example of that is by implementing the Conceptual Problem-Solving approach in the 5E Learning Cycle (Diyana et al, 2020). Then, in order to identify the difficulties found by students, there certainly needs to be other aspects of mutual learning in addition to these learning techniques (Elisa et al, 2019).…”
Section: Questionmentioning
confidence: 99%